Plasmodium vivax MSP1-42 kD Variant Proteins Detected Naturally Induced IgG Antibodies in Patients Regardless of the Infecting Parasite Phenotype in Mesoamerica - Lilia Gonzalez-Ceron; Barbara Dema; Olga L. Palomeque-Culebro; Frida Santillan-Valenzuela; Alberto Montoya; Arturo Reyes-Sandoval (Life, 2023)
Background: The serological tests using blood stage antigens might be helpful for detecting recent exposure to Plasmodium parasites, and seroepidemiological studies would aid in the elimination of malaria. This work produced recombinant proteins of PvMSP142 variants and evaluated their capacity to detect IgG antibodies in symptomatic patients from Mesoamerica. Methods: Three variant Pvmsp142 genes were cloned in the pHL-sec plasmid, expressed in the Expi293F™ eukaryotic system, and the recombinant proteins were purified by affinity chromatography. Using an ELISA, 174 plasma or eluted samples from patients infected with different P. vivax haplotypes were evaluated against PvMSP142 proteins and to a native blood stage antigen (NBSA). Results: The antibody IgG OD values toward PvMSP142 variants (v88, v21, and v274) were heterogeneous (n = 178; median = 0.84 IQR 0.28–1.64). The correlation of IgG levels among all proteins was very high (spearman’s rho = 0.96–0.98; p < 0.0001), but was lower between them and the NBSA (rho = 0.771; p < 0.0001). In only a few samples, higher reactivity to the homologous protein was evident. Patients with a past infection who were seropositive had higher IgG levels and lower parasitemia levels than those who did not (p < 0.0001). Conclusions: The PvMSP142 variants were similarly efficient in detecting specific IgG antibodies in P. vivax patients from Mesoamerica, regardless of the infecting parasite’s haplotype, and might be good candidates for malaria surveillance and epidemiological studies in the region.